NUMERICAL MODELLING AND SIMULATION OF CO2 –ENHANCED COAL-BED METHANE RECOVERY (CO2-ECBMR): THE EFFECT OF COAL SWELLING ON GAS PRODUCTION PERFORMANCE - Ferian Anggara; Kyuro Sasaki; Yuichi Sugai (Geological Engineering Department Universitas Gadjah Mada, 2015)
This presents study investigate the effect of swelling on gas production performances at coal reservoirs during CO2-ECBMR processes. The stressdependent permeability-models to express effect of coal matrix shrinkage/swelling using Palmer and Mansoori (P&M) and Shi and Durucan (S&D) models were constructed based on present experimental results for typical coal reservoirs with the distance of 400 to 800 m between injection and production wells. By applying the P&M and S&D models, the numerical simulation results showed that CH4 production rate was decreasing and peak production time was delayed due to effect of stress and permeability changes caused by coal matrix swelling. The total CH4 production ratio of swelling effect/no-swelling was simulated as 0.18 to 0.95 for permeability 1 to 100 mD, respectively. It has been cleared that swelling affects gas production at permeability 1 to 15 mD, however, it can be negligible at permeability over 15 mD.